Cultural considerations in Asian and Pacific Islander American mental health - Grey, Harvette; Hall-Clark, Brittany N. (Oxford University Press, 2015)
"In America's increasingly diverse society, it is imperative that mental health providers prioritize the development of their cultural competence to assure that they are equipped to meet the needs of their clients. Cultural Considerations in Asian and Pacific Islander American Mental Health offers a broad array of perspectives from clinicians and researchers actively working with racially/ethnically diverse populations. This book addresses psychosocial cultural issues that impact the mental health of the growing Asian American population. The book opens with the concept of what and who is an Asian American, as well as the myriad distinctions and differences among various Asian groups. Covered chapter topics include a historical overview of the diverse populations among Asian and Pacific Islander Americans; a discussion of the tensions and similarities between empirically supported treatments and cultural competence; Asian and Pacific Islander American elders and depression; and a psychodynamic perspective regarding the treatment of dual diagnosis with an Asian American client. This book is a must-read for mental health clinicians, students, community workers, school counselors, and nurses who work with diverse populations."--Google books viewed Feb. 2, 2021.